Who do you want to be when you grow old? : the path of purposeful aging - Leider, Richard; Shapiro, David A., 1957- (Berrett-Koehler Publishers, Inc., 2021)
"Our later years need not be a time of loss. This book helps readers embrace the positive possibilities of aging and provides guidance on doing so purposefully, with courage, compassion, and curiosity"--